The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1143/jjap.30.l1359
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Microwave Properties of Tl2Ba2CaCu2O8 Thin Films on NdGaO3

Abstract: High-quality epitaxial Tl2Ba2CaCu2O8 superconducting thin films have been grown on NdGaO3(001) by a two step process. One film, annealed at 850°C, shows interdiffusion of Ga by secondary ion mass spectroscopy, resulting in an incomplete AC susceptibility transition at 80 K. For films annealed at lower temperature, excellent crystallinity and transport properties were obtained. Ground plane substitution of the film in a 5 GHz microstrip resonator indicated worse microwave performance than similar films on LaAlO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 10 publications
0
2
1
Order By: Relevance
“…8) indicates that only a small fraction of the film consists of these grains, which are about 0.1 mm in length. In the previous study by Young etal., 12 the majority of the film surface was covered with a-axis oriented grains, compared to less than 5% of the surface in this study.…”
Section: Ndgaocontrasting
confidence: 58%
See 1 more Smart Citation
“…8) indicates that only a small fraction of the film consists of these grains, which are about 0.1 mm in length. In the previous study by Young etal., 12 the majority of the film surface was covered with a-axis oriented grains, compared to less than 5% of the surface in this study.…”
Section: Ndgaocontrasting
confidence: 58%
“…In one previous study of Tl 2 Ba 2 CaCu 2 0 8 on LaA10 3 , the rocking curve full width at half maximum has been reported to be as narrow as 0.3 °, 8 although the same group has reported values to be more typically in the range O.8-1.O 0 . 12 The T c of the Tl 2 Ba 2 CaCu 2 0 8 film on LaA10 3 was measured inductively and by ac magnetic susceptibility to be 103 K. In previous studies T c has been reported to be 102 K, 8 103 K, 7 and 106.5 K. 6 The narrow transition width in the inductive measurement of T c is the signature of a high quality film with few weak junctions between grains. SNMS analysis gave no indication of any reaction between the film and the substrate.…”
Section: B Laaiomentioning
confidence: 96%
“…Oxide materials of general composition ABCO 4 (where A ¼ Ca, Sr, Ba, B ¼ La, Nd, Pr and C ¼ Al, Ga) with the tetragonal perovskite-related K 2 NiF 4 -type structure are considered promising substrate materials for high-temperature superconducting (HTSc) thin films, elements of thermal radiation receivers and other electronic devices due to their electrochemical and thermal properties and good lattice matching [1][2][3][4][5][6][7][8]. Crystals of high structural quality are required for such applications so the characterisation of crystal lattice defects is of great importance.…”
Section: Introductionmentioning
confidence: 99%